Somos Americanos? The potential of the Inter-american Human Rights System for Indigenous Justice in Canada - Gold, Sara (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional)

(untitled) (Société québécoise de droit international, 2022)
This paper explores how Canada’s full commitment to the Inter-American Human Rights System (IAS) could provide a further recourse for monitoring, protecting and promoting Indigenous rights in Canada. Presenting the Americas as a united continent, it emphasizes how reconceptualising what it means to “be American” can help Canadians think about their connection, comprehension and acceptance of this regional system. This paper examines the Canadian government’s historical disinterest in the IAS and establishes this as the primary reason for its current lack of commitment. It argues that Canada’s ratification of the American Convention on Human Rights and recognition of the Inter-American Court of Human Rights jurisdiction would positively impact the rights of Indigenous peoples living within its borders. It concludes by highlighting a Canadian initiative that is working towards making Canada a better player in the IAS and contends that the Canadian government should follow their lead.